“A Concealed Malignancy” A Case Series of Primary Fallopian Tube Carcinoma and its Diagnostic Challenges - Sereño, Lorene Kate M.; Billod, Jimmy A (Asian Pacific Journal of Cancer Care, 2024)
Background: Primary fallopian tube carcinoma remains a diagnostic challenge due to its rarity and nonspecific clinical presentation. Its insidious nature often leads to misdiagnosis, with the true diagnosis emerging only on histopathology. This case series presents four cases of fallopian tube cancer managed in our institution over a five-year period, highlighting the diverse clinical presentations and diagnostic hurdles. Methods and Results: The four cases, encompassing a range of ages, exhibited distinct symptoms. The first case, a 44-year-old patient, presented with recurrent vaginal discharge followed by supraclavicular node involvement suggestive of metastasis. The second case, a 58-year-old patient, presented with vaginal spotting and a pelvic mass mimicking an ovarian tumor. The third and fourth cases, a 71-year-old and a 66-year-old respectively, presented with gradually enlarging abdominal masses, initially attributed to an adnexal mass. Intraoperative findings revealed a thinned and dilated fallopian tube in the first and third cases, an unidentified right fallopian tube with an adnexal mass in the second case, and a left fallopian tube transformed into a tan, irregular mass in the fourth case. Histopathology confirmed high-grade fallopian tube serous carcinoma in all cases. This case series emphasizes the importance of raising suspicion for primary fallopian tube carcinoma in patients with suggestive clinical features. Timely investigations and early detection are crucial for effective management and improving patient outcomes. Conclusion: This study underscores the varied presentation of this rare malignancy and serves as a reminder to avoid misdiagnosis and ensure prompt and appropriate treatment strategies.